Forecasting inflation: A comparison of the ECB's short-term inflation projections and inflation-linked swaps - Jetro Anttonen; Olli-Matti Laine (Bank of Finland, 2024)
According to the efficient-market hypothesis, forecasts derived from efficient market prices should be unbeatable. However, numerous institutions, including the European Central Bank, regularly publish forecasts for future inflation that deviate from market expectations. We investigate the relative predictive accuracy of the ECB's short-term inflation projections against predictions derived from the market prices of short-term inflation-linked swaps (fixings) in 2018-2023. We show that the predictive accuracy of fixings and the ECB projections have been very comparable during times of low and stable inflation, but during recent times of economic volatility the market prices of fixings have provided significantly more accurate predictions. We find that the efficiency of financial markets to process new information may result in more accurate short-term inflation forecasts than produced by Eurosystem insiders, and that risk premia and market inefficiencies do not seem to play a significant role in the context of short-term inflation-linked swaps. Overall, our findings suggest that making use of the information in the market prices for fixings could potentially improve the accuracy of the ECB's short-term inflation projections.
urn.fi/URN:NBN:fi-fe2024110890199
Keywords: E31; G14; G17; 330; Inflation; fixings; swaps; financial market; forecasting